Roles of membrane trafficking in plant cell wall dynamics - Ebine, Kazuo; Ueda, Takashi (Frontiers in Plant Science, 2015)
The cell wall is one of the characteristic components of plant cells. The cell wall composition differs among cell types and is modified in response to various environmental conditions. To properly generate and modify the cell wall, many proteins are transported to the plasma membrane or extracellular space through membrane trafficking, which is one of the key protein transport mechanisms in eukaryotic cells. Given the diverse composition and functions of the cell wall in plants, the transport of the cell wall components and proteins that are involved in cell wall-related events could be specialized for each cell type, i.e., the machinery for cell wall biogenesis, modification, and maintenance could be transported via different trafficking pathways. In this review, we summarize the recent progress in the current understanding of the roles and mechanisms of membrane trafficking in plant cells and focus on the biogenesis and regulation of the cell wall.